Cellular distribution of dopamine D1 and D2 receptors in rat medial prefrontal cortex - Vincent, SL (J Neurosci, 1993)
The relative distribution and cellular localization of the dopamine D1 and D2 receptor subtypes were assessed in frozen sections of rat medial prefrontal cortex (mPFC). The D1 and D2 receptor binding sites were labeled with the selective high-affinity antagonists SCH 23390 and N-(p- aminophenethyl)-spiperone (NAPS), respectively, coupled to either Bodipy or Texas red fluorophores. Under the incubation conditions employed, kinetic, competition, and selectivity studies showed that these modified ligands retained pharmacological selectivity. Optimal binding fluorescence was at 100 nM of each ligand, and fluorescence increased linearly from 1 to 15 min of incubation at 2 degrees C. NAPS- Texas red binding fluorescence was inhibited with 10 nM quinpirole (D2 agonist), but not 10 nM SKF 38393 (D1 agonist), while SCH 23390-Texas red binding was inhibited with SKF 38393, but not quinpirole. The localization of dopamine receptor binding was assessed in montages constructed from low-magnification photomicrographs through the depth of the cortex, or in corresponding high-magnification photomicrographs. Cells showing D1- or D2-like receptor binding fluorescence were present in layers II-VI, with the highest density observed in layers V and VI. The addition of mianserin (100 nM, 5-HT2 antagonist) to incubated sections slightly reduced the numbers of labeled cells in each cortical layer, but retained the preferential localization to the deeper layers. Two separate observations supported the idea that the fluorescently coupled ligands were localized to neuronal cell bodies. First, receptor labeling with the fluorescently coupled ligands co-localized almost exclusively to cells in the cortical mantle showing neuron-specific enolase immunoreactivity. Second, a comparison of the cell size distribution taken from adjacent Nissl-stained sections with the size of cells showing D1- or D2-like receptor binding fluorescence revealed complete overlapping of fluorescence with neuronal cell bodies. In mPFC layer VI, the size of cells showing D1-like receptor binding fluorescence was 77.8 +/- 5.1 microns2, similar to non-pyramidal neurons, while that for D2-like receptor binding fluorescence was 108.2 +/- 4.5 microns2, consistent with both large interneurons and small pyramidal cells. Only a small percentage of cells showing D1- or D2- like receptor binding overlapped in size with glia, but this occurred almost exclusively within the white matter region below the cortical mantle. These findings are consistent with the hypothesis that the D1 and D2 receptor subtypes are found on different populations of neurons, although some overlap probably occurs.(ABSTRACT TRUNCATED AT 400 WORDS)